(untitled) (Fiep Bulletin - online, 2015)
This essay constitutive a approach of the understanding of the part culture Brazilian’s Indians people into concept white men. The subject here is the esthetic between “Beauty” and the “Savage” its colors and punctual forms potential zed by surprise of the beauty art, so in the ornament and adornment witch in the exposition of the body’s nude, decorates, paints, non-mystified into nature, however, mythified into form of the literature.